Evidence for nutrient-dependent regulation of the COPII coat by O-GlcNAcylation. (15th June 2021) - Bisnett, Brittany J; Condon, Brett M; Linhart, Noah A; Lamb, Caitlin H; Huynh, Duc T; Bai, Jingyi; Smith, Timothy J; Hu, Jimin; Georgiou, George R; Boyce, Michael
Abstract: O-linked β- N -acetylglucosamine (O-GlcNAc) is a dynamic form of intracellular glycosylation common in animals, plants and other organisms. O-GlcNAcylation is essential in mammalian cells and is dysregulated in myriad human diseases, such as cancer, neurodegeneration and metabolic syndrome. Despite this pathophysiological significance, key aspects of O-GlcNAc signaling remain incompletely understood, including its impact on fundamental cell biological processes. Here, we investigate the role of O-GlcNAcylation in the coat protein II complex (COPII), a system universally conserved in eukaryotes that mediates anterograde vesicle trafficking from the endoplasmic reticulum. We identify new O-GlcNAcylation sites on Sec24C, Sec24D and Sec31A, core components of the COPII system, and provide evidence for potential nutrient-sensitive pathway regulation through site-specific glycosylation. Our work suggests a new connection between metabolism and trafficking through the conduit of COPII protein O-GlcNAcylation.